Murmurs: the journal of art and healing - Danilewitz, Marlon; Zumrova, Andrea; Bloom, Lynn; Blaskovits, Farriss (Canadian Medical Education Journal, 2019)
In an era of unprecedented physician burnout and disconnection, there is growing recognition of the importance of integrating the study of humanities in medicine. Emerging research has underscored the importance of reflective writing and creativity in bolstering physician resilience. The publication “Murmurs Magazine,” therefore, should be of great interest to medical educators. This publication was developed and continues to be managed by medical students as a forum for creative expression and reflection.